Innovative environment-friendly coastal restoration techniques for enchancement of eco-tourism potential in coastal areas - Ismail, Hadibah (2004)
In the context of sustainable development along the coast, particularly for the nurturing of eco-tourism potential in a coastal area, engineering works associated with tourism-related activities including shore protection, beach creation, recreational marine parks, marinas, etc have a considerable impact on the health of the marine ecosystem. Traditional methods of building "hard" structures are currently recognized as not environment-friendly. On the other hand "soft" methods such as artificial beach nourishment and non-structural solutions despite getting popular, have their own setbacks. Ironically, marine ecosystem services afforded by natural systems such as mangroves, seagrass beds and coral reefs provide protection against floods and storms, reduction of shoreline retreat and riverbank erosion as well as maintenance of biodiversity. Hence a new outlook into the dimensions of these ecosystem services must be integrated into design features of coastal engineering structures in order for them to have added values in the design. This paper describes the state-of-the-art overview of a number of recen developments in the design of environment-friendly coastal restoration techniques that emulate those natural functions of the marine ecosystem Several research work and products employing these innovative human intenventions would enhance the marine ecosystem services and thus sustain the coastal environment for eco-tourism per se.